2022
DOI: 10.3389/fsurg.2022.898172
|View full text |Cite
|
Sign up to set email alerts
|

Early Predictive Value of NT-proBNP Combined With Echocardiography in Anthracyclines Induced Cardiotoxicity

Abstract: ObjectiveDetermine the predictive value of N-terminal pro-B-type natriuretic peptide (NT-proBNP) combined with echocardiography in the diagnosis of anthracyclines-induced chronic cardiotoxicity.MethodsA total of 80 female breast cancer patients from January 2019 to October 2021 were included in our hospital. Twenty-six patients with cardiotoxicity were divided into the cardiac impairment group, and the 54 patients without cardiotoxicity were classified into the normal control group. NT-proBNP levels and cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The studies focusing on the role of natriuretic peptides (NPs) in predicting and/or detecting CTRCD in breast cancer patients [ 86 , 87 , 90 , 91 , 92 , 96 , 97 , 98 , 99 , 100 , 101 , 103 , 105 , 106 , 109 , 113 , 114 , 117 , 118 , 119 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 ], as identified in the review, are shown in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies focusing on the role of natriuretic peptides (NPs) in predicting and/or detecting CTRCD in breast cancer patients [ 86 , 87 , 90 , 91 , 92 , 96 , 97 , 98 , 99 , 100 , 101 , 103 , 105 , 106 , 109 , 113 , 114 , 117 , 118 , 119 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 ], as identified in the review, are shown in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the contribution of troponins, NT-proBNP or BNP, and LVEF and associated parameters in detecting and monitoring CTRCD is undoubtable, but additional studies are required in order to define their exact roles to predict CTRCD. The studies focusing on the role of LVEF, strain changes, and other imaging biomarkers in predicting and/or detecting CTRCD in breast cancer patients [ 84 , 91 , 94 , 95 , 99 , 108 , 109 , 113 , 118 , 119 , 130 , 131 , 132 , 133 , 137 , 139 , 141 , 142 , 146 , 147 , 148 , 149 , 150 , 151 , 153 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation